The Role Of The Sharia Supervisory Board (DPS) In Supervision Of Contract Implementation At The Binjai Branch Bri Sharia - Abi Waqqosh; Fani hairani yusfa; Sri Sudiarti; Tri Dessy Fadillah; Haris Al Amin (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This study aims to determine the position and function of DPS in contract making, supervision of contract implementation, and the effectiveness of contract supervision at Bank BRI Syariah Binjai Branch. In this research, the researcher conducted research using qualitative methods. Research that uses a qualitative approach aims to explore or build a proportion or explain the meaning behind reality. Researchers are based on reality or events that take place in the field. Qualitative research methods can be interpreted as research that produces descriptive data, regarding spoken and written words, and observable behavior of the people being studied. Qualitative research is also research that produces descriptions in the form of words or verbally from the phenomenon under study or from people who are competent in their fields. The results of this study are that the position and function of the DPS in drafting the BRI Syariah Bank contract is appropriate. In general, what is being done is to supervise all forms of activities related to existing contracts in the bank. This supervision also takes the form of standardizing and ratifying contract standards that apply nationally in the sense that it applies to all BRI Syariah branches, as well as assisting parties in disseminating information to BRI Syariah branches in the regions.